Impact response and energy absorption of functionally graded foam under temperature gradient environment - Liu, Hu (2022)
As an effective strategy to enhance the energy absorption and impact resistance capacities of foam materials, density-gradient design has been widely proposed as a viable solution. However, the influence of thermal environment on the impact response and energy absorption of functionally graded foam still remains unclear. In the present paper, an analytical model based on the double shock wave theory is presented to examine the impact performance of density-graded foam rods under temperature gradient environments. A density-graded foam with one end supported and the other end struck by a block of mass is presented to evaluate their impact performances. Both the positive and negative density-gradient models with power-law profiles along the axial direction of the foam rod are considered. The proposed theoretical representation is validated against several previous models, including a finite element (FE) simulation. It is demonstrated that the temperature gradient may lead to transformations in the deformation pattern for the positive and negative density-graded foams. Moreover, the temperature gradient can enlarge the impact resistance property in most cases and can reduce the energy absorption capacity of density-graded foams.